A REVIEW DYNAMIC VIBRATION ON DRILL STRING IN DRILLING OPERATION - Afriansyah Afriansyah; Hasan Basri (Sebatik, 2019)
For decades, researchers have investigated the phenomenon of vibrations in drilling activities. One of the interesting things is the vibration in the drillstring. Vibration might be caused by Interfere with each other between the drilling mud and drilling string, contact forces between the drillstring and wellbore, and interfere with each other between bit and wellbore that can ruin the drilling equipment, the drillstring and/or the stabilizers. This paper presents several experiments in different methods to predict vibrations of drill string in the drilling operation. There are three types of vibration in drilling operation. First, axial vibration generated from interaction between bottom hole and bit. Second, Torsional vibration that excited from resonance of drill collar, bit chatter, stick slip between formation and bit and modal coupling. Third, lateral vibration that excited from interaction between formation and bit, imbalance of mass, whirl of bit, and from force of fluid around drill string. One or whole type of these vibration can vibrate the drillstring and it result damage of drillstring as reperesent by decrease in rate of penetration or damage of bit. In this paper, we will compare several methods to predict deflection, natural frequencies, and trajectory or orbital during impact for finite element method, differential quadrature method, and multibody dynamic method. Result show that all method can be used for calculating deflection, Finite element method and differential quadrature method for account natural frequencies, multi dynamic method for calculate trajectory during impact. However, for simple method to calculate or predict vibration used Differential Quadrature method. The future work will involve investigation on vibration in drillstring with combine several method